2020
DOI: 10.47162/rjme.61.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and histopathological changes in placentas of pregnancies with intrauterine growth restriction

Abstract: This is an open-access article distributed under the terms of a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International Public License, which permits unrestricted use, adaptation, distribution and reproduction in any medium, non-commercially, provided the new creations are licensed under identical terms as the original work and the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In the present study, intervillous fibrin was significantly increased in the IUGR group than in the control group. This is consistent with the results of other studies ( Nigam et al, 2014 , Visan et al, 2020 ). The presence and expansion of intervillous fibrin are strongly correlated with a reduction in placental and fetal weight ( Redline 2008 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, intervillous fibrin was significantly increased in the IUGR group than in the control group. This is consistent with the results of other studies ( Nigam et al, 2014 , Visan et al, 2020 ). The presence and expansion of intervillous fibrin are strongly correlated with a reduction in placental and fetal weight ( Redline 2008 ).…”
Section: Discussionsupporting
confidence: 94%
“…IUGR may be affected by maternal, fetal, or placental factors ( Sharma, Shastri and Sharma 2016 ); however, placental factors are considered essential causes in many IUGR cases ( Visan et al 2020 ). Studies have revealed the association of IUGR with placental changes, such as placental weight, fetal/placental weight ratio, type of umbilical cord insertion in the placenta, and its diameter ( Visan, Balan, Costea, Carauleanu, Haba, Haba, Socolov, Mogos, Bogdanici, Nemescu, Tanase, Turliuc, Cucu, Scripcariu, Toma, Popovici, Ciocoiu and Petrariu 2020 ). A small placenta is associated with an increased risk of IUGR ( Ducray et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a placental infarct consists of necrosis of a foetal cotyledon caused by occlusion of the supplying uteroplacental artery. However, as previously mentioned in the method section, placental infarcts are areas of low T2 signal or sometimes high T2 intensity with low signal rim, usually in the background of presence of a thick placenta [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the very common causes of growth restriction is the placental factor because placental structure and function affect the transport and exchange of gases and nutrients, as well as the products of metabolism at the level of uteroplacental circulation [3]. Ultrasound fetal measurements and other markers present the most common diagnostic method for prediction and diagnosing of FGR.…”
Section: Introductionmentioning
confidence: 99%